Experimental Study on Boiler Scales Cleaning Using Hydrochloric and Citric Acids - Dina Raheem; Janet Lazer (Engineering and Technology Journal, 2012)
The effect of hydrochloric acid and citric acid was studied experimentally for boiler chemical cleaning to determine the dissolved scale by using carbon steel samples of water-side boiler tubes sections ,different concentrations of hydrochloric acid HCL and citric acid were used (2%,3%,4% and 5%) to calculate the weight loss of samples then determined the dissolved scale in gm/m2. The more efficient acid for the chemical cleaning, was found to be HCL acid at 5% concentration by using 0.3% rodin inhibitor at temp. 60 and time 30 minute to obtain 248 gm/m2 of dissolved scale while the citric acid at 5% concentration by using 0.3% hexamine inhibitor and temp.70 and time 240 minute to obtain 168 gm/m2 of scale dissolved.